Mineral-based cobalt catalyst and preparation method and application thereof
By preparing mineral-based cobalt catalysts on dolomite support, the problems of insufficient activity and stability and high cost of traditional cobalt catalysts in water organic pollutant treatment are solved, and efficient and environmentally friendly organic pollutant degradation effect is achieved to meet sewage Emission standards.
Patent Information
- Application Number
- CN202411350228.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-26
AI Technical Summary
In the prior art, when treating organic pollutants in water bodies, especially under conditions of wide pH application range and stability requirements, the catalytic activity and stability of cobalt catalysts are insufficient, and traditional preparation methods have problems of wastewater and high costs.
The mineral-based cobalt catalyst is prepared by dissolving a mixture of metal cobalt salt and anhydrous ethanol by calcining, using natural alkaline earth metal mineral dolomite as a support, and the activation effect of cobalt catalyst is enhanced by temperature-controlled calcining. Stability, reduce Co ion leaching, achieve low cobalt ion leaching and high catalytic activity.
It achieves efficient degradation of organic pollutants, meets sewage discharge standards, reduces catalyst production costs, has green and environmentally friendly characteristics, and improves the atomic utilization rate and catalytic activity of cobalt.
Smart Images

Figure BDA0005062150490000051 
Figure BDA0005062150490000052 
Figure BDA0005062150490000061
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of natural mineral-based environmental catalytic materials and preparation and application thereof, and in particular relates to a mineral-based cobalt catalyst and a preparation method and application thereof. Background Art
[0002] With the rapid development of industries such as medicine, energy and chemicals, various new pollutants may be discharged during product manufacturing and use. These pollutants come from a wide range of sources, most of which are persistently toxic, have hidden exposure risks and are difficult to effectively decompose and treat.
[0003] In order to deal with the organic pollution problem in water bodies, advanced oxidation technologies such as Fenton oxidation, persulfate oxidation, electrochemical oxidation, photocatalysis and ozone oxidation have attracted much attention. 5 The new advanced oxidation technology (SR-AOPs) based on cobalt-based catalysts (such as sulphuric acid, peroxymonosulfate, PMS) has a wide pH range (pH = 2 to 9) and has the advantage of stability when degrading organic pollutants. At present, researchers have developed a variety of cobalt-based catalysts and used materials such as carbon nanotubes and graphene as well as natural minerals such as kaolin and calcite to improve their efficiency. Compared with other artificial synthetic materials, natural non-metallic minerals are widely available and relatively cheap, and have great potential in further developing or improving their application prospects in catalytic reactions.
[0004] Therefore, in-depth exploration and full utilization of the advantages of natural non-metallic resources will become one of the key research directions to achieve better environmental pollution purification effects. Summary of the invention
[0005] The present invention aims to provide a mineral-based cobalt catalyst and a preparation method and application thereof. The mineral-based cobalt catalyst has the characteristics of low cobalt ion leaching and high catalytic activity.
[0006] The technical solution of the present invention is as follows:
[0007] A method for preparing a mineral-based cobalt catalyst comprises the following steps:
[0008] (1) weighing a metal cobalt salt and dissolving it in a solvent to obtain a metal cobalt salt solution;
[0009] The metal cobalt salt is selected from Co(NO 3 ) 2 6H 2 O、CoCl 2 6H 2 O. CoSO 4 7H 2O, cobalt acetate, cobalt acetylacetonate, disodium ethylenediaminetetraacetate cobalt salt hydrate, cobalt oxalate, cobalt phthalocyanine or a mixture of two thereof, preferably CoCl 2 6H 2 O;
[0010] The solvent is selected from anhydrous ethanol, deionized water or a mixture of the two, preferably anhydrous ethanol;
[0011] The molar volume ratio of the metal cobalt salt to the solvent is 1:70-80, mol / L; preferably 1:80, mol / L;
[0012] (2) adding natural alkaline earth metal mineral to the metal cobalt salt solution obtained in step (1), stirring evenly, placing in a 50-70° C. water bath and stirring for 6-12 h, filtering and drying to obtain a solid powder;
[0013] The natural alkaline earth metal mineral is selected from one or a mixture of dolomite, brucite, and olivine. In the embodiment of the present invention, dolomite is selected;
[0014] The mass volume ratio of the natural alkaline earth metal mineral to the metal cobalt salt solution is 1:11.1-16.7, g / mL; preferably 1:16.7, g / mL;
[0015] The preferred water bath temperature is 60°C and the stirring time is 6h;
[0016] The preferred drying temperature is 60-70°C;
[0017] (3) calcining the solid powder obtained in step (2) under air or nitrogen atmosphere, wherein the calcination conditions are: heating rate of 2 to 5° C. / min, annealing at 400 to 500° C. for 2 h, and naturally cooling to room temperature to obtain the mineral-based cobalt catalyst;
[0018] Preferably, the solid powder is placed in a covered crucible for calcination under a nitrogen atmosphere;
[0019] Preferred calcination conditions: heating rate 5°C / min, annealing at 500°C for 2h.
[0020] The invention relates to a mineral-based cobalt catalyst prepared by the preparation method.
[0021] The present invention also relates to the use of the mineral-based cobalt catalyst in activating persulfate (PMS) to degrade organic pollutants;
[0022] The catalytic degradation function of the mineral-based cobalt catalyst of the present invention is achieved by activating persulfate. Therefore, those skilled in the art can expect that any organic pollutant that can be degraded by PMS is within the protection scope of the present invention; specific organic pollutants are, for example, one or more of metronidazole, 5-fluorouracil, norfloxacin, tetracycline, and ciprofloxacin; in one embodiment of the present invention, the organic pollutant is metronidazole.
[0023] The specific application methods are as follows:
[0024] The mineral-based cobalt catalyst is dispersed in an aqueous solution of organic pollutants, and persulfate is added for stirring and degradation;
[0025] In the aqueous solution of organic pollutants, the concentration of organic pollutants is 5 to 50 mg / L, preferably 20 mg / L;
[0026] The persulfate is selected from potassium hydrogen persulfate and potassium persulfate;
[0027] The mass volume ratio of the mineral-based cobalt catalyst to the aqueous solution of the organic pollutant is 0.2 to 2:1, g / L; preferably 0.5:1, g / L;
[0028] The mass volume ratio of persulfate to organic pollutant aqueous solution is 0.25-2:1, g / L, preferably 0.5:1, g / L.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] 1. The mineral-based cobalt catalyst prepared by the present invention uses natural minerals as carriers to load amorphous cobalt catalysts, which can disperse cobalt and prevent cobalt particle agglomeration, increase active sites, and improve the atomic utilization rate and catalytic activity of cobalt.
[0031] 2. The mineral-based cobalt catalyst prepared by the present invention uses a soluble inorganic cobalt salt as a precursor, does not require an additional organic cobalt ligand (or complexing agent), is prepared by a simple impregnation and calcination method, and no waste water or waste liquid is generated during the process.
[0032] 3. The mineral-based cobalt catalyst prepared by the present invention uses dolomite as a carrier, which can enhance the effect of the cobalt catalyst in activating PMS, and can effectively control the leaching of Co ions (<1 mg / L), meeting the limit value specified in the "Comprehensive Sewage Discharge Standard" (GB8978-1996), while helping to reduce the production cost of the catalyst, having green and environmentally friendly characteristics, and being conducive to large-scale application.
[0033] 4. The present invention can significantly improve the stability of cobalt in the mineral-based cobalt catalyst and reduce the leaching of Co ions during the catalytic process by temperature-controlled calcination.
[0034] 5. Compared with the preparation methods of traditional cobalt catalysts (such as element doping, porous carbon loading of cobalt, and cobalt-o-phenanthroline ligand regulation of loading), the mineral-based cobalt catalyst prepared by the present invention has the advantages of high catalytic activity and low environmental risk.
[0035] 6. The cobalt catalyst loaded on the surface of dolomite in the present invention has an amorphous structure, which can increase the catalytic active sites and utilize the synergistic effect of the catalytic PMS activity of dolomite itself to show excellent degradation and removal efficiency for organic pollutants.
[0036] 7. The mineral-based cobalt catalyst prepared by the present invention has the advantage of high catalytic efficiency compared to other transition metal catalysts prepared based on dolomite (such as dolomite-based copper catalyst). BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 : XRD spectra of the composite material Co@B prepared in Example 1, the composite material Co@BL prepared in Comparative Example 10, and dolomite.
[0038] Figure 2 : Local energy dispersion X-ray spectrum of the composite material Co@BKS prepared in Example 2; wherein, (a) is the local electron image of Co@BKS; (b) is the C element mapping; (c) is the Ca element mapping; (d) is the Mg element mapping; (e) is the O element mapping; and (f) is the Co element mapping. DETAILED DESCRIPTION
[0039] The present invention is further described below by means of specific embodiments, but the protection scope of the present invention is not limited thereto.
[0040] In the following embodiments,
[0041] CoCl 2 6H 2 O was from Aladdin Biochemical Technology Co., Ltd.; CuCl 2 From Aladdin Biochemical Technology Co., Ltd.; Al(NO 3 ) 3 9H 2 O comes from Aladdin Biochemical Technology Co., Ltd.; dolomite powder comes from Guzhang County Shanlin Shiyu Mineral Products Co., Ltd.; calcium carbonate powder comes from Aladdin Biochemical Technology Co., Ltd.; magnesite powder comes from Guzhang County Shanlin Shiyu Mineral Products Co., Ltd.
[0042] Example 1
[0043] (1) Take 0.238 g (0.001 mol) CoCl 2 6H 2 O, dissolved in 80 mL of anhydrous ethanol to obtain a mixed solution A.
[0044] (2) Add 4.8 g of dolomite powder to the mixed solution A, stir well, and place in a 60° C. constant temperature water bath for 6 h. After filtering, dry at 60° C. to obtain powder B.
[0045] (3) Powder B was placed in a covered crucible and heated in nitrogen at 500°C and 5°C min -1 The mixture was annealed at a heating rate for 2 h and naturally cooled to room temperature to obtain Co@B.
[0046] Example 2
[0047] (1) Take 0.238 g (0.001 mol) CoCl 2 6H 2 O, dissolved in 80 mL of deionized water to obtain a mixed solution A.
[0048] (2) Add 4.8 g of dolomite powder to the mixed solution A, stir well, and place in a 60° C. constant temperature water bath for 6 h. After filtering, dry at 60° C. to obtain powder B.
[0049] (3) Powder B was placed in a covered crucible and heated in air at 500°C and 5°C min -1 The sample was annealed at a heating rate for 2 h and then naturally cooled to room temperature to obtain Co@BKS.
[0050] Example 3
[0051] (1) Take 0.476 g (0.002 mol) CoCl 2 6H 2 O, dissolved in 80 mL of deionized water to obtain a mixed solution A.
[0052] (2) Add 4.8 g of dolomite powder to the mixed solution A, stir well, and place in a 60° C. constant temperature water bath for 6 h. After filtering, dry at 60° C. to obtain powder B.
[0053] (3) Powder B was placed in a covered crucible and heated in air at 500°C and 5°C min -1 The mixture was annealed at a heating rate for 2 h and naturally cooled to room temperature to obtain 2Co@BKS.
[0054] Example 4
[0055] (1) Take 0.238 g (0.001 mol) CoCl 2 6H 2 O, dissolved in 80 mL of anhydrous ethanol to obtain a mixed solution A.
[0056] (2) Add 4.8 g of dolomite powder to the mixed solution A, stir well, and place in a 60° C. constant temperature water bath for 6 h. After filtering, dry at 60° C. to obtain powder B.
[0057] (3) Powder B was placed in a covered crucible and heated in nitrogen at 400°C and 5°C min -1 The sample was annealed at a heating rate for 2 h and then naturally cooled to room temperature to obtain Co@400B.
[0058] Comparative Example 1
[0059] (1) Take 0.238 g (0.001 mol) CoCl 2 6H 2 O, dissolved in 80 mL of anhydrous ethanol to obtain a mixed solution A.
[0060] (2) Add 4.8 g of dolomite powder to the mixed solution A, stir well, and place in a 60° C. constant temperature water bath for 1 h. After filtering, dry at 60° C. to obtain powder B.
[0061] (3) Powder B was placed in a covered crucible and heated in nitrogen at 500°C and 5°C min -1 The temperature was raised and annealed for 2 h, and then naturally cooled to room temperature to obtain Co@B 1h .
[0062] Comparative Example 2
[0063] (1) Take 0.238 g (0.001 mol) CoCl 2 6H 2 O, 0.96 g of o-phenanthroline was dissolved in 80 mL of anhydrous ethanol to obtain a mixed solution A, which was fully stirred and placed in a 60°C constant temperature water bath for 6 h. After filtering, the solution was dried at 60°C to obtain a powder B.
[0064] (2) Powder B was placed in a covered crucible and heated in nitrogen at 500°C and 5°C min -1 The mixture was annealed at a heating rate for 2 h and naturally cooled to room temperature to obtain Co@L.
[0065] Comparative Example 3
[0066] (1) Take 0.238 g (0.001 mol) CoCl 2 6H 2 O, dissolved in 80 mL of anhydrous ethanol to obtain a mixed solution A.
[0067] (2) Add 4.8 g of calcium carbonate powder to the mixed solution A, stir well, and place in a 60° C. constant temperature water bath for 6 h. After filtering, dry at 60° C. to obtain powder B.
[0068] (3) Powder B was placed in a covered crucible and heated in nitrogen at 500°C and 5°C min -1 The temperature was raised and annealed for 2 h, and then naturally cooled to room temperature to obtain Co@CaCO3 .
[0069] Comparative Example 4
[0070] (1) Take 0.238 g (0.001 mol) CoCl 2 6H 2 O, dissolved in 80 mL of anhydrous ethanol to obtain a mixed solution A.
[0071] (2) 4.8 g of dolomite powder was added to the mixed solution A, and the mixture was stirred well and placed in a 60° C. constant temperature water bath for 6 h. After filtering, the mixture was dried at 60° C. to obtain powder B. In this comparative example, powder B was directly used for subsequent degradation experiments and was named B.
[0072] Comparative Example 5
[0073] (1) Place dolomite powder in a covered crucible and heat in nitrogen at 500°C, 5°C min -1 The sample was annealed at a rate of increasing temperature for 2 h and naturally cooled to room temperature to obtain 500B.
[0074] Comparative Example 6
[0075] (1) Take 0.134 g (0.001 mol) CuCl 2 , dissolved in 80 mL of anhydrous ethanol to obtain a mixed solution A.
[0076] (2) Add 4.8 g of dolomite powder to the mixed solution A, stir well, and place in a 60° C. constant temperature water bath for 6 h. After filtering, dry at 60° C. to obtain powder B.
[0077] (3) Powder B was placed in a covered crucible and heated in nitrogen at 500°C and 5°C min -1 The mixture was annealed at a heating rate for 2 h and naturally cooled to room temperature to obtain Cu@B.
[0078] Comparative Example 7
[0079] (1) Take 0.238 g (0.001 mol) CoCl 2 6H 2 O, dissolved in 80 mL of anhydrous ethanol to obtain a mixed solution A.
[0080] (2) Add 4.8 g of dolomite powder to the mixed solution A, stir well, and place in a 60° C. constant temperature water bath for 6 h. After filtering, dry at 60° C. to obtain powder B.
[0081] (3) Powder B was placed in a covered crucible and heated in nitrogen at 800°C and 5°C min -1 The sample was annealed at a heating rate for 2 h and then naturally cooled to room temperature to obtain Co@800B.
[0082] Comparative Example 8
[0083] (1) Take 0.238 g (0.001 mol) CoCl 2 6H 2 O, 0.375 g (0.001 mol) Al(NO 3 ) 3 9H 2 O, dissolved in 80 mL of anhydrous ethanol to obtain a mixed solution A.
[0084] (2) Add 4.8 g of dolomite powder (Guzhang County Shanlin Shiyu Mineral Products Co., Ltd.) to the mixed solution A, stir well, and place in a 60°C constant temperature water bath for 6 h. After filtering, dry at 60°C to obtain powder B.
[0085] (3) Powder B was placed in a covered crucible and heated in nitrogen at 500°C and 5°C min -1 The mixture was annealed at a heating rate for 2 h and naturally cooled to room temperature to obtain CoAl@B.
[0086] Comparative Example 9
[0087] (1) Take 0.238 g (0.001 mol) CoCl 2 6H 2 O, dissolved in 80 mL of anhydrous ethanol to obtain a mixed solution A.
[0088] (2) Add 7.2 g of dolomite powder to the mixed solution A, stir well, and place in a 60° C. constant temperature water bath for 6 h. After filtering, dry at 60° C. to obtain powder B.
[0089] (3) Powder B was placed in a covered crucible and heated in nitrogen at 500°C and 5°C min -1 The temperature was raised and annealed for 2 h, and then naturally cooled to room temperature to obtain Co@B 7.2 .
[0090] Comparative Example 10
[0091] (1) Take 0.238 g (0.001 mol) CoCl 2 6H 2 O, 0.96 g of o-phenanthroline, was dissolved in 80 mL of anhydrous ethanol to obtain a mixed solution A.
[0092] (2) Add 4.8 g of dolomite powder to the mixed solution A, stir well, and place in a 60° C. constant temperature water bath for 6 h. After filtering, dry at 60° C. to obtain powder B.
[0093] (3) Powder B was placed in a covered crucible and heated in nitrogen at 500°C and 5°C min -1 The sample was annealed at a heating rate for 2 h and then naturally cooled to room temperature to obtain Co@BL.
[0094] Comparative Example 11
[0095] (1) Take 0.238 g (0.001 mol) CoCl 2 6H 2 O, dissolved in 80 mL of anhydrous ethanol to obtain a mixed solution A.
[0096] (2) Add 4.8 g of magnesite powder to the mixed solution A, stir well, and place in a 60° C. constant temperature water bath for 6 h. After filtering, dry at 60° C. to obtain powder B.
[0097] (3) Powder B was placed in a covered crucible and heated in nitrogen at 500°C and 5°C min -1 The sample was annealed at a heating rate for 2 h and then naturally cooled to room temperature to obtain Co@LM.
[0098] Application comparison experiment
[0099] 1. Catalytic degradation test of organic matter: A 20 mg / L metronidazole solution was prepared to simulate an organic pollutant, and 0.025 g of the samples of Examples 1-4 and Comparative Examples 1-11 were respectively placed in 50 mL of the metronidazole solution, and 0.025 g of potassium persulfate (PMS) was added. After reacting for 5 min, a small amount of the solution was taken for solid-liquid separation, and the absorbance of the residual metronidazole in the solution was tested by an ultraviolet spectrophotometer. The degradation rate of the sample to metronidazole was calculated, as shown in Table 1.
[0100] 2. Co ion leaching test: After continuing to stir the reaction for 30 minutes, the filtered degradation reaction solution was taken to test the Co ion leaching concentration, as shown in Table 2.
[0101] Table 1 Sample degradation rate data table
[0102]
[0103] Table 2 Sample Co leaching data
[0104]
[0105]
[0106] 1. Examples 1-4 in Table 1 illustrate that the dolomite-based catalyst prepared by the present invention can achieve efficient degradation of target organic matter within only 5 minutes.
[0107] 2. Examples 1-4 in Table 2 show that the Co ion leaching level in the dolomite-based catalyst is within the limit specified in GB8978-1996 (<1 mg / L).
[0108] 3. By comparing Example 1 and Comparative Example 1 in Table 1, it can be shown that reducing the water bath time (1 h) will reduce the catalytic performance of the dolomite-based catalyst.
[0109] 4. By comparing Example 1 and Comparative Example 4 in Table 1, it can be shown that the performance efficiency of dolomite alone in degrading organic pollutants is relatively low.
[0110] 5. By comparing Example 1 and Comparative Example 5 in Table 1, it can be shown that the performance efficiency of 500°C calcined dolomite in degrading organic pollutants alone is relatively low.
[0111] 6. By comparing Example 1 and Comparative Example 6 in Table 1, it can be shown that the catalytic performance of the Co-based dolomite catalyst is significantly better than that of the Cu-based dolomite catalyst.
[0112] 7. By comparing Example 1 and Comparative Example 8 in Table 1, it can be shown that the catalytic performance of the Co-based dolomite catalyst is significantly better than that of the CoAl-based dolomite catalyst.
[0113] 8. By comparing Example 1 and Comparative Example 3 in Table 1, it can be shown that using calcium carbonate as a carrier will reduce the catalytic performance of the cobalt catalyst.
[0114] 9. By comparing Example 1 and Comparative Example 11 in Table 1, it can be shown that using magnesite as a carrier will reduce the catalytic performance of the cobalt catalyst.
[0115] 10. By comparing Example 1 and Comparative Example 2 in Table 1, it can be shown that replacing dolomite with the organic substance o-phenanthroline will reduce the catalytic performance of the cobalt catalyst.
[0116] 11. By comparing Example 1 and Comparative Example 10 in Table 1, it can be shown that adding the organic substance o-phenanthroline will reduce the catalytic performance of the cobalt catalyst.
[0117] 12. By comparing Example 1 and Comparative Example 9 in Table 1, it can be shown that reducing the amount of Co will reduce the catalytic performance of the dolomite-based catalyst.
[0118] 13. By comparing Example 1, Example 4 and Comparative Example 7 in Table 1, it can be shown that increasing the calcination temperature (800° C.) will reduce the catalytic performance of the dolomite-based catalyst.
[0119] Figure 1 The composite material Co@B prepared in Example 1, the composite material Co@BL prepared in Comparative Example 10, and dolomite XRD spectra. Figure 1 It can be seen that Co@B and Co@BL almost retain the characteristic peaks of dolomite. However, no crystal signal peaks of Co are shown in the XRD spectrum, which may be caused by the low doping content of cobalt elements, which is conducive to inhibiting the leaching of Co ions.
[0120] Figure 2 The local energy dispersive X-ray spectrum (EDS) of the composite material Co@BKS prepared in Example 2, where (a) is the local electron image of Co@BKS; (b) is the C element mapping; (c) is the Ca element mapping; (d) is the Mg element mapping; (e) is the O element mapping; and (f) is the Co element mapping. Figure 2 It can be seen that the composition of the Co@BKS sample is consistent with the components of Ca, C, Mg, O, Co and is evenly distributed. The presence of the Co element indicates that Co@BKS successfully captures Co ions without particles or agglomeration, indicating that the active Co is evenly distributed on the dolomite surface.
Claims
1. A method for preparing a mineral-based cobalt catalyst, characterized in that: The steps include: (1) weighing a metal cobalt salt and dissolving it in a solvent to obtain a metal cobalt salt solution; (2) adding natural alkaline earth metal mineral to the metal cobalt salt solution obtained in step (1), stirring evenly, placing in a 50-70° C. water bath and stirring for 6-12 h, filtering and drying to obtain a solid powder; The natural alkaline earth metal mineral is selected from one or a mixture of two of dolomite, brucite and olivine; (3) In an air or nitrogen atmosphere, the solid powder obtained in step (2) is calcined under the following calcination conditions: a heating rate of 2 to 5°C / min, annealing at 400 to 500°C for 2h, and naturally cooling to room temperature to obtain the mineral-based cobalt catalyst.
2. The method for preparing a mineral-based cobalt catalyst according to claim 1, characterized in that: In step (1), the metal cobalt salt is selected from one or a mixture of two of Co(NO3)2·6H2O, CoCl2·6H2O, CoSO4·7H2O, cobalt acetate, cobalt acetylacetonate, disodium ethylenediaminetetraacetate cobalt salt hydrate, cobalt oxalate, and cobalt phthalocyanine.
3. The method for preparing a mineral-based cobalt catalyst according to claim 1, characterized in that: In step (1), the solvent is selected from anhydrous ethanol, deionized water, or a mixture of the two.
4. The method for preparing a mineral-based cobalt catalyst according to claim 1, characterized in that: In step (1), the molar volume ratio of the metal cobalt salt to the solvent is 1:70-80, mol / L.
5. The method for preparing a mineral-based cobalt catalyst according to claim 1, characterized in that: In step (2), the mass volume ratio of the natural alkaline earth metal mineral to the metal cobalt salt solution is 1:11.1-16.7, g / mL.
6. A mineral-based cobalt catalyst prepared according to the preparation method according to any one of claims 1 to 5.
7. Use of the mineral-based cobalt catalyst as claimed in claim 6 in activating persulfate to degrade organic pollutants.
8. The use according to claim 7, characterized in that The organic pollutants are: one or more of metronidazole, 5-fluorouracil, norfloxacin, tetracycline, and ciprofloxacin.
9. The use according to claim 7, characterized in that The application method is as follows: The mineral-based cobalt catalyst is dispersed in an aqueous solution of organic pollutants, and persulfate is added for stirring and degradation; In the aqueous solution of organic pollutants, the concentration of organic pollutants is 5 to 50 mg / L; The persulfate is selected from potassium hydrogen persulfate and potassium persulfate; The mass volume ratio of the mineral-based cobalt catalyst to the aqueous solution of the organic pollutant is 0.2 to 2:1, g / L; The mass volume ratio of persulfate to organic pollutant aqueous solution is 0.25-2:1, g / L.
Citation Information
Patent Citations
Activated carbon supported cobalt oxide catalyst and application of same in organic pollutant degradation
CN102580746A
Precious metal-free dolomite catalyst and preparation method and application thereof
CN110935453A
Porous layered montmorillonite confinement cobalt oxide catalyst as well as preparation method and application thereof
CN118527145A
Process for the preparation of a catalyst useful for the polymerization of olefins
US3663660A
Circulating fluid bed combustion with CO combustion promoter and reduced combustion air
US4927348A